2018
DOI: 10.3892/or.2018.6477
|View full text |Cite
|
Sign up to set email alerts
|

Upregulated miR‑20a‑5p expression promotes proliferation and invasion of head and neck squamous cell carcinoma cells by targeting of TNFRSF21

Abstract: MicroRNAs (miRNAs) play important roles in regulation of proliferation, migration, and invasion of head and neck squamous cell carcinoma (HNSCC). The present study assessed expression, functions and mechanisms of miR‑20a‑5p in the regulation of HNSCC cell proliferation, migration and invasion. miR‑20a‑5p expression in HNSCC cell lines and tissues was detected using qRT‑PCR, while miR‑20a‑5p mimics and inhibitor were transfected into HNSCC cells for assessment of the effects using different assays (CCK‑8, wound… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 34 publications
1
15
0
Order By: Relevance
“…Zong et al 63 found that the overexpression of SDC3 can significantly inhibit the proliferation and metastasis of mesenchymal tumor cells. Wu et al 64 found that miR20a-5p promotes the proliferation, migration, and invasion of head and neck squamous cell carcinoma by down-regulating TNFRSF21. Another study found that TNFRSF21 also plays an important role in regulating leukocyte infiltration 65 .…”
Section: Discussionmentioning
confidence: 99%
“…Zong et al 63 found that the overexpression of SDC3 can significantly inhibit the proliferation and metastasis of mesenchymal tumor cells. Wu et al 64 found that miR20a-5p promotes the proliferation, migration, and invasion of head and neck squamous cell carcinoma by down-regulating TNFRSF21. Another study found that TNFRSF21 also plays an important role in regulating leukocyte infiltration 65 .…”
Section: Discussionmentioning
confidence: 99%
“…MiR-145-5p was reported to inhibit the proliferation of rat mesangial cells (RMCs) and vascular smooth muscle cells (VSMCs) by targeting different genes [49,50]. Protein phosphatase 3 catalytic subunit alpha is encoded by PPP3CA, and Ding et al [51] found that overexpressing hsa-miR-145-5p significantly reduced the mRNA expression of PPP3CA, which likely affected the cell cycle and invasion of the laryngeal squamous cell carcinoma (LSCC) cell line Tu-177.…”
Section: Discussionmentioning
confidence: 99%
“… 46 Wu et al 2018 studied Upregulated miR-20a-5p expression in HNSCC cells and observed downregulation of TNFRSF21 expression. 47 …”
Section: Apoptotic Genes and Its Molecular Biologymentioning
confidence: 99%